Studi Awal Amplifikasi Gerak Tanah Gempa untuk Universitas Indonesia (Depok) - Lucky Suryajaya, Lingga Ekaputra; Prakoso, Widjojo Adi; Basarah, Yuamar Imarrazan; Pramono, Sigit (Institut Teknologi Bandung, 2024)
Abstract This research is motivated by the frequent occurrence of earthquakes in Indonesia in recent years. Meanwhile, the common practice in determining soil and seismic parameters in Indonesia still heavily relies on various empirical studies. Therefore, this study aims to investigate soil and seismic parameters in Indonesia through the phenomenon of earthquake ground motion amplification, with a case study located at the University of Indonesia (Depok). The research methods employed include the analysis of earthquake recording data in the UI Forest at a depth of 300 meters, one-dimensional modeling using DEEPSOIL v7 software, and a comparative analysis of the ground motion recording results of the earthquake in Banten on January 14th, 2022, with a magnitude of 6.6 (low strain) on the surface of UI Forest and FMIPA UI. The research results show visible oscillations at the end of the ground acceleration output and a spike in the peak ground acceleration (PGA) value at around 30 meters in the uppermost layer, with periods and spectral acceleration higher than the expected recorded values. This indicates that the soil modeled based on correlation is softer than anticipated. In other words, the soil is stiffer than previously assumed based on the established correlations.